2021
DOI: 10.21037/apm-20-831
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of electro-acupuncture combined with dyclonine hydrochloride in relieving the side effects of gastroscopy: a controlled trial

Abstract: Background: The present study aimed to explore the effectiveness of electro-acupuncture (EA) in combination with a local anesthetic used in Western medicine in preventing the side effects of gastroscopy.Methods: A sample group of 150 patients were divided into three groups based on treatment methods: an EA group, a dyclonine hydrochloride mucilage group, and a combined treatment group. In the EA group, EA stimulation was given at the Hegu, Neiguan, and Zusanli acupoints; in the dyclonine hydrochloride mucilage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Liao et al found that the inspection effect of magnetic control capsule endoscopy is comparable to that of traditional gastroscope, and the subjects have better tolerance [ 7 ]. Chen et al found that acupuncture can reduce the adverse reactions related to gastroscopy [ 8 ], and this study found that nasal breathing can reduce the incidence of nonanalgesic and sedative gastroscopy-related adverse reactions.…”
Section: Discussionmentioning
confidence: 70%
“…Liao et al found that the inspection effect of magnetic control capsule endoscopy is comparable to that of traditional gastroscope, and the subjects have better tolerance [ 7 ]. Chen et al found that acupuncture can reduce the adverse reactions related to gastroscopy [ 8 ], and this study found that nasal breathing can reduce the incidence of nonanalgesic and sedative gastroscopy-related adverse reactions.…”
Section: Discussionmentioning
confidence: 70%
“…The causes of bad mood can be summarized as follows: (a) gastroscopy is an invasive examination, and patients who do not know much about it think that the operation will damage the throat and esophagus and are unwilling to cooperate with the examination; (b) in the process of examination, patients are prone to cough, nausea, and vomiting due to physical stimulation of gastroscope; (c) patients lack relevant knowledge about the monitoring of gastric cancer, the importance of gastroscopy, and the operation procedure of gastroscopy, especially for the first time. Therefore, during the nursing of gastroscopy, attention should be paid to the health guidance and emotional guidance of patients [20][21][22][23][24]. In this study, the mode group adopted the mode of knowledge, belief, and behavior nursing, which mainly applied the acquisition of knowledge, belief, and practice before the gastroscopy and process of gastroscopy and examination.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients could not tolerate examination and had to bear anesthesia-related complications. In addition, patients who did not meet the anesthesia requirements could not complete gastroscopy [14]. Currently, there are many studies on EGV in cirrhosis.…”
Section: Discussionmentioning
confidence: 99%